Staying the Course: Reflections on the Progress and Challenges of the UHC Law in the Philippines - Pura Angela Co; Ileana Vîlcu; Denese De Guzman; Eduardo Banzon (Health Systems & Reform)
The Philippine Universal Health Care (UHC) law enacted in 2019 aimed to address entrenched health system challenges to achieving equitable access to quality health care. This commentary discusses the progress in its implementation to meet its objectives. Some of these health system challenges include overlapping financing roles; weak incentives for integrating health services across local government units (LGUs), the inclusion of the private sector in networks of care, and fragmented primary health care services. The UHC law introduced reforms to transform the Philippine Health Insurance Corporation (PhilHealth) into a strategic purchaser of health services, expand population coverage, and prioritize comprehensive outpatient and primary care services. Furthermore, the law mandated bolstering subnational health financing through a Special Health Fund (SHF) intended to encourage LGUs to integrate into provincial or city health systems. Pilots of the SHF highlighted opportunities and challenges in pooling, prioritizing, and redistributing resources if local health systems are capacitated. Despite facing implementation challenges, including changing priorities, politics, and lack of resources, the Philippines' experience emphasizes the importance of adaptive leadership, sustained commitment, and effective stakeholder engagement to ensure that these health financing reforms remain objective-oriented. Maximizing the UHC law’s potential going forward requires addressing ongoing challenges: sustained resource generation, ensuring effective coverage of the poor, and capacitating local health systems. The journey of the Philippines toward UHC offers valuable insights for global health reformers, underscoring the need for adaptive approaches and active political engagement to sustain and achieve progress toward universal and equitable health care access.